Advancement and Maintenance of Infant Incubator in Medokan Ayu Health Centre Surabaya for Effort to Kepp Continuity of Serive - Syaifudin, Syaifudin; Kholiq, Abdul; Lamidi, Lamidi (Frontiers in Community Service and Empowerment, 2023)
Health Development is a leading program among 45 important programs that must be carriedout throughout the country related to sectoral and regional development, where the health program is in 12thplace. Health programs in the city of Surabaya are carried out through puskesmas. One of the servicesavailable at the Medokan Ayu Health Center (PKM) is interchangeable rooms. At the Medokan AyuSurabaya Health Center, there is also a delivery room, as well as infant incubator equipment for babies bornprematurely. Baby incubator makes the percentage of babies born safe and the ability to survive fromhypothermia higher in premature infants. The increasing sophistication of medical devices raises questionsabout device safety and reliability of infant incubator tools, hence the importance of controlled parameterinspection in medical devices. safety inspection and performance is performed by clinical professionals. Atthe community health center for maintenance activities it is not yet reached because there are no staff tohandle it. In community service, carrying out maintenance activities for infant incubator equipment aims toensure that the infant incubator is ready and suitable for use so that services can continue. From the results ofthe activities, infant incubators have been produced which are in good condition and ready and fit for use.From the measurement results, it was found that the biggest error when the infant incubator was set at 36oCwas -0.69oC and 0.86 at 34oC